Effects of Dehydration on Freezing Characteristics and Survival in Liquid Nitrogen of Three Recalcitrant Seeds - Hor, Yue Luan; Stanwood, P. C.; Chin, H. F. (1990)
The recalcitrant seeds rambutan( Nephelium lappaceum). durian (Durio zibethinus) and cempedak (Artocarpus inleger) have a high critical moisture content (below which ·rapid loss of viability occurs of 27.0%, 26.0% and 37.9%,respectively. The critical moisture for embroys were higher at 39.0% for rambutan, 53.9% for durian and 43.2% for Cempedak. Differential Thermal analysis of the embroyos confirmed that their threshhold moistures (below which there is no freezable water) were lower than their critical moistureS. The Threshhold moistures for rambutan, durian and cempedak embryos were approximately 30%, 32% and 33% respectively. It is suggested that unsuccessful attempts at cryopreservation of embroyos of 'recalcitrant seeds in the past maybe due to the absence of safe window between the high critical moisture content and the threshhold moisture. This results in freezing injury at the higher moistures and dehydration injury' at the lower moistures. Potential techniques to overcome this and improve cryopreservation of recalcitrant seed embryos are discussed.